2011
DOI: 10.1007/s10611-011-9297-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining the links between animal abuse and human violence

Abstract: Empirical research has increasingly found evidence for the coexistence of animal abuse and various forms of interpersonal violence. Some researchers have even argued for a specific version of this relationship, namely, that individuals tend to move from violence toward animals, particularly in childhood, to subsequent violence toward humans. Others have suggested that the evidence for this graduation or progression hypothesis is weak and inconsistent, and that an approach to animal abuse that focuses on the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 46 publications
(55 reference statements)
1
61
0
13
Order By: Relevance
“…In modern conditions, they are sent to the slaughterhouse after 3-4 years of "work". Modern milk cow under the influence of intensive technologies produces 10 times more milk than in natural conditions [11].…”
Section: ахметов радмир рустемович -студент кафедра транспорта и храmentioning
confidence: 99%
“…In modern conditions, they are sent to the slaughterhouse after 3-4 years of "work". Modern milk cow under the influence of intensive technologies produces 10 times more milk than in natural conditions [11].…”
Section: ахметов радмир рустемович -студент кафедра транспорта и храmentioning
confidence: 99%
“…In this regard, he points to the important role that theology and philosophy have played in the study of our treatment of other animals. Similarly, Beirne (1999) argues that the human abuse of other animals is a vital area for study in criminology, and Flynn (2000and Flynn ( , 2011 comments that sociology can make a significant contribution to the study of cruelty to other animals and its links with abuse of humans. In what remains of this chapter I point to a number of ways in which the abuse of other animals is important, and indeed essential, to sociological analysis.…”
Section: The Other Animal As a 'Wronged Subject'mentioning
confidence: 99%
“…They found that the majority of the youths in their small-scale study who belonged to a youth gang used dogs for protection and companionship, and utilized them to enhance their own status. Over 20 types of abuse of other animals were described by the participants in the research (Maher and Pierpoint, 2011), and it is well known that the abuse of other animals is a serious aspect of antisocial behaviour (Flynn, 2000(Flynn, , 2011. Flynn notes that this is especially so amongst males because, he observes, 'Like some of the other antisocial behaviours, animal cruelty may be rewarded by peer groups, and for males, linked with developing and proving one's masculinity' (Flynn, 2000, p. 88).…”
Section: The Abuse Of Other Animals and Human Criminal Identitymentioning
confidence: 99%
“…It has already been supported that there is a positive relation between animal cruelty and violence (from homicide to family violence) [33] [34] [35] [36] [37]. Dominant hypotheses on this issue are that overflowing aggressiveness or hatred against human beings is supposed to occur on animals or that the same violence which is directed against human beings of society in general, is also directed against animals.…”
Section: Introductionmentioning
confidence: 99%